Menilik Dasar Hukum dan Hikmah Akad Gadai dalam Nilai Islam Rahmatan Lil Alamin - Nicho Hadi Wijaya (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2021)
The presence of Islam as a religion revealed by Allah SWT to the Prophet Muhammad SAW certainly aims to create goodness in the world and in the hereafter. In achieving this goal, the Al-Qur'an has arranged various matters regarding how to create an Islam that is Rahmatan Lil Alamin. One of the obvious forms of this is the existence of orders to aid others without asking for added value to the assistance given. The commandment is contained in the Al-Qur'an surah Al-Baqarah 282-283. However, they are still ordered to prepare an object to be used as collateral for debt, this contract is then called rahn (pawn). That is, in a pawning contract the value of helping fellow human beings is implemented. In addition, there are also things that can prevent bad things in the future by having objects that are used as collateral for the pawning contract. So then from the pawning agreement, it can be seen how Islam is present as a blessing for all nature, the meaning of grace is to provide real goodness in the form of living both in the world and the hereafter with three indicators: prosperity, peace, and happiness.